Studies on the Germination and Growth of Cotton and Groundnut Seeds Irrigated by Distillery Spentwash - Chidankumar3, S. Chandraju1*, Siddappa2; C.S. (Current Botany, 2011)
Germination of Cotton and Ground nut seeds was made by irrigated with distillery spentwash of different concentration. The spentwash i.e. primary treated spentwash [PTSW] 1:1, 1:2 and 1:3 spentwash were analyzed for their plant nutrients such as nitrogen, phosphorous, potassium and physical & chemical characteristics. Experimental soil was tested for its chemical physical parameters. Cotton and Ground nut seeds were sowed in the prepared land and irrigated with raw water (RW), 1:1, 1:2 and 1:3 (SW: RW) spentwash. The nature of germination of seeds was studied. It was found that, the germination was good (100%) in 1:3 SW irrigation, while very poor in 1:1 SW (25%), moderate in 1:2 SW (80%) and 95% in RW irrigations.